Selective isolation and antagonistic activity of actinomycetes from mangrove forest of Pahang, Malaysia - Zainal Abidin, Zaima Azira; Abdul Malek, Nurfathiah; Zainuddin, Zarina; Khan Chowdhury, Ahmed Jalal (Taylor & Francis, 2016)
This study aimed to isolate and evaluate the antagonistic potential of actinomycetes from mangrove forest of Pahang, Malaysia. Sediment samples from seven different sites were pretreated using wet heat and dry heat methods followed by dilution plating on eight isolation media. In total, 4850 isolates were successfully recovered, with inorganic salt–starch agar displaying the highest percentage of recovery (31.7%), followed by actinomycete isolation agar (24.1%). The wet heat pretreatment was found to be more effective in the enumeration of actinomycetes, since 81.4% of total isolates were yielded using this technique, whereas dry heat treatment was better in the enumeration of spore-forming actinomycetes. After both pretreatments, Streptomyces-like and Micromonospora-like isolates were the most predominant. The antagonistic activities of the representative isolates were evaluated using the cross-streak method. In total, 78 isolates were active against at least one of the test organisms. Among them, 28.2% exhibited antibacterial activity, 23.1% exhibited antifungal activity and 48.7% displayed both. Nine isolates demonstrated broad antagonism by inhibiting the growth of all test organisms. The presence of a relatively large number of bioactive isolates suggests that Pahang mangrove forest is a potential source of actinomycetes with biosynthetic capabilities